2022
DOI: 10.2147/sccaa.s356763
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins Profiling in Umbilical Cord Mesenchymal Stem Cell-Derived Secretome

Abstract: Background Umbilical cord mesenchymal stem cells (UC-MSCs)-derived secretome is currently used in regenerative therapy. MSCs are believed to secrete a wide spectrum of bioactive molecules which give paracrine effects in immunomodulation and regenerative capacities. One group that was found in secretome is interleukins (ILs), a cytokine that plays an essential role in the process of proliferation, differentiation, maturation, migration, and adhesion of immune cells. However, as there are many types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, the UC-MSC secretome is characterized by the presence of angiogenic factors, reduced levels of metalloproteinases (MMPs), and elevated synthesis of transforming growth factor β 1 (TGF-β1), chemokines, and anti-inflammatory cytokines, with interleukyn-6 (IL-6) being one of the most secreted. These characteristics suggest that the UC-MSC secretome presents the ability to control inflammatory responses [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the UC-MSC secretome is characterized by the presence of angiogenic factors, reduced levels of metalloproteinases (MMPs), and elevated synthesis of transforming growth factor β 1 (TGF-β1), chemokines, and anti-inflammatory cytokines, with interleukyn-6 (IL-6) being one of the most secreted. These characteristics suggest that the UC-MSC secretome presents the ability to control inflammatory responses [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…After cleavage, mediated by metalloproteinases, this protein functions as an antagonist of chemotaxis and cell activation [32]. Pro-inflammatory cytokines such as IL1b, IL8 [11,12], IL6, IL-1a, interferon (IFN)-γ, and tumor necrosis factor α (TNFα) [33] and IL-9 [35] were also found in the secretome.…”
Section: Secretome Composition 21 Soluble Factorsmentioning
confidence: 99%
“… 3–5 Upregulation of pro and anti-inflammatory cytokines and chemokines can certainly be used as immunomodulators. 5 Increased neurotrophic factor would be very beneficial for nerve cell regeneration. 3 …”
Section: Dear Editormentioning
confidence: 99%
“…Characterization of stem cells could provide information about the type of stem cells that produced these growth factors (FGF, PDGF, VEGF, and TGF-β1).Other studies have reported that cytokines and growth factors secretion from MSCs originating from gingival, adipose tissue, umbilical cord or Wharton's jelly tend to increase in a hypoxic microenvironment. [3][4][5] Upregulation of pro and anti-inflammatory cytokines and chemokines can certainly be used as immunomodulators. 5 Increased neurotrophic factor would be very beneficial for nerve cell regeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation